KESULITAN MAHASISWA CALON GURU FISIKA DALAM MEREPRESENTASIKAN KONSEP LISTRIK MAGNET - Wahyuni Handayani; Wawan Setiawan; P Sinaga; Andi Suhandi (Journal of Teaching and Learning Physics, 2017)
Communication in science is multimodal (verbal and visual). Representation skills are one of the communication skills in science. A physics teacher is required to have representation skills so that the students more easily to acsess the concept that they have to lean and the teacher  communicate physics concepts more easily to his students. This study examines the representation skills of preservice physics teacher. Three aspects of representation skills, that examined are: 1) the skill of making a single mode representation, 2) the skills of translation between representation modes and 3) multi-representation skills. The instrument used to measure representation skills has been validated and used to measure representation skills of preservice physics teacher in Listrik-Magnet courses. The results showed that the preservive physics student have difficulty in making all of the aspect of representation. It is occured because there has never been learning related to representation or assessment skills that specifically test their representation skills